Pengaruh K3 (Keselamatan dan Kesehatan Kerja) dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Perindustrian dan Perdagangan Lembah Karet Padang - Cici Mayora (Politeknik Kampar, 2024)
The purpose of this study was to determine and analyze the effect of occupational safety and health (OSH) and the work environment on employee performance at PT. Perindustrian dan Perdagangan Lembah Karet Padang. The population in this study were all employees of PT. Perindustrian dan Perdagangan Lembah Karet Padang were 244 people. Determining the number of samplesby using the formula Slovin, then the number of respondents as a sample in this study were 152 respondents. The data analysis technique used is multiple linear regression analysis and for hypothesis testing using statistical t test. The results showed that: Occupational safety and health partially significant effect on employee performance. Occupational Health and Safety has t arithmetic 9.271 > t table 1.9761 or sig value. is 0.000 < 0.05. Work environment partially significant effect on employee performance. Work environment has t arithmetic 2.383 > t table 1.9761 or sig value. its value is 0.018 < 0.05.